Prosocial Behavior and Policy Spillovers: A Multi-Activity Approach - Claes Ek (Lund University, School of Economics and Management, Department of Economics, 2016)
Observing that people who wish to engage in prosocial behavior are often presented with more than one means to the same end, we develop a model in which agents may contribute to a single public good through a range of different activities. We use this model to make two points. First, noting that effort on one activity has been argued to reduce (moral licensing) as well as increase (moral consistency) effort on other activities, we derive sufficient conditions under which policy to facilitate one activity partially crowds out effort on other activities. Second, we use an example to argue that a given single-activity model may be extended to multiple activities in several alternative ways, and that not all generalizations need reproduce the ideas and results of the original model; in general, careful thinking is needed to determine which multi-activity model is appropriate.
Keywords: D03; D11; H41; 330; public goods; prosocial behavior; moral licensing; self-image